QORAQALPOQ TILI FRAZEOLOGIYASINI QIYOSIY OʻRGANISHNING BA’ZI MASALALARI - Kurboniyazov, G.A. (SCIENCE and SOCIETY, 2025)
The article provides a scientific review of the works studied in recent years on the comparison of the phraseology of the Karakalpak language with other languages.